A Dendritic Supramolecular Complex as Uniform Hybrid Micelle with Dual Structure for Bimodal In Vivo Imaging. Issue 12 (28th December 2016) - Zhang, Simin; Zheng, Yanmei; Yin, Shengyan; Sun, Jingzhi; Li, Bao; Wu, Lixin
Abstract: In this study, a uniform complex dual micelle bearing a gadolinium‐substituted polyoxometalate core, a hydrophobic middle, and a biocompatible organic shell, which exhibits a uniform size and definite molecular weight and chemical composition, is constructed through a simple two‐step process for use as a fluorescence and magnetic resonance imaging (MRI) contrast agent. A paramagnetic polyoxometalate cluster, K13 [Gd(β2 ‐SiW11 O39 )2 ], is first encapsulated with a cationic 3‐generation dendron (D ‐3) bearing triethylene glycol monomethyl ether terminal groups through ionic substitution. The formed electrostatic complex, (D ‐3)13 [Gd(β2 ‐SiW11 O39 )2 ] (D ‐GdSiW), which displays an ambivalent micellar structure, is then demonstrated to act as a suitable carrier for the uptake of cationic fluorescent dyes, forming a loaded complex. The dye‐loaded complexD ‐GdSiW‐D is thus proven to display high relaxivity as a contrast agent, maintaining its structural stability under physiological conditions with low cell cytotoxicity. Confocal laser scanning microscopic observation also demonstrates the fluorescence imaging property of the prepared complex upon consumption by MCF‐7 cells. Both in vivo fluorescence imaging and MRI further confirm that the complex micelle with dual micellar structure may be a suitable liver‐specific contrast agent for clinical diagnosis. Abstract : Dendritic encapsulation : A complex dual micelle bearing a paramagnetic polyoxometalate, hydrophobic middle and biocompatible periphery is constructed by encapsulating the cluster with cationic dendrons through ionic substitution. The dual micellar structure of the complex in water acts as a suitable carrier for the uptake of dyes for fluorescent and magnetic resonance imaging (see figure). Both in vitro and in vivo observations confirm the bimodal liver‐specific contrast agent for possible clinical diagnosis.